Relative efficiency of RAS versus least squares methods of updating input-output structures - addendum - Henry, EW (Economic & Social Studies, 1974)
The following note is intended to clarify both the mathematical derivation of the Least-Squares minimum and its interpretation, as given in the author's paper, published in the October 1973 issue of this Review. I am grateful to D r Richard Lecomber o f the Department o f Economics, University of Bristol, for drawing my attention to the point at issue, and for his paper having some new proposals for updating transactions.
Keywords: RAS; Least squares regression